The elements of making: a social practice perspective for everyday creators - Risner, Isabelle; Gauntlett, David; Culpepper, Mary Kay (Creativity Studies, 2022)
In contrast to behavioural approaches that attempt to explain creativity, social practice theories commonly emphasize aspects of the material world that shape and reproduce how people engage with them. How might social practice theory clarify how making affects millions of hobbyist creators – and what makes making matter to them? This article examines the theoretical work tying creativity to social practice. It then reports on a project in which small groups of everyday creators in the United Kingdom (n = 95) gathered in workshops to discuss their experiences and opinions regarding the materials, meanings, and competences of making. A model-making research method instigated peer discussion revealing both individual and shared accounts of practice. The data indicated that participants, regardless of practice, experienced creating as an ongoing performance providing many benefits that promote personal and societal transformation. With our graphic iteration of the elements of making, we assert that the meanings these makers attached to their various do-it-yourself practices were underscored by the materials they worked with and the competences they built in creating.